Determine o valor da função afim f(x)= -3 x + 4 para: X=1, X= 1/3, X=0, X=K+1
Soluções para a tarefa
Respondido por
401
Para
:
Primeiro substituimos
com
:
![-3\cdot1 + 4 -3\cdot1 + 4](https://tex.z-dn.net/?f=-3%5Ccdot1+%2B+4)
Agora, é só fazer:
![-3\cdot1 = -3 -3\cdot1 = -3](https://tex.z-dn.net/?f=-3%5Ccdot1+%3D+-3)
![-3 + 4 = 1 -3 + 4 = 1](https://tex.z-dn.net/?f=-3+%2B+4+%3D+1)
Então:
.
Para
:
Substituindo
com
:
![-3\cdot\frac{1}{3} + 4 -3\cdot\frac{1}{3} + 4](https://tex.z-dn.net/?f=-3%5Ccdot%5Cfrac%7B1%7D%7B3%7D+%2B+4)
Fazendo:
![-3\cdot\frac{1}{3} = -1 -3\cdot\frac{1}{3} = -1](https://tex.z-dn.net/?f=-3%5Ccdot%5Cfrac%7B1%7D%7B3%7D+%3D+-1)
![-1 + 4 = 3 -1 + 4 = 3](https://tex.z-dn.net/?f=-1+%2B+4+%3D+3)
Então:![f(\frac{1}{3}) = 3 f(\frac{1}{3}) = 3](https://tex.z-dn.net/?f=f%28%5Cfrac%7B1%7D%7B3%7D%29+%3D+3)
Para
:
Substituindo
com
:
![-3\cdot0 + 4 -3\cdot0 + 4](https://tex.z-dn.net/?f=-3%5Ccdot0+%2B+4)
Fazendo:
![-3\cdot0 = 0 -3\cdot0 = 0](https://tex.z-dn.net/?f=-3%5Ccdot0+%3D+0)
![0 + 4 = 4 0 + 4 = 4](https://tex.z-dn.net/?f=0+%2B+4+%3D+4)
Então:![f(0) = 4 f(0) = 4](https://tex.z-dn.net/?f=f%280%29+%3D+4)
Para
:
Substituindo
com
:
![-3\cdot(k + 1) + 4 -3\cdot(k + 1) + 4](https://tex.z-dn.net/?f=-3%5Ccdot%28k+%2B+1%29+%2B+4)
Distribuíremos
por
.
![-3(k + 1) = -3 - 3 k -3(k + 1) = -3 - 3 k](https://tex.z-dn.net/?f=-3%28k+%2B+1%29+%3D+-3+-+3+k)
![-3 - 3k + 4 -3 - 3k + 4](https://tex.z-dn.net/?f=-3+-+3k+%2B+4)
Agruparemos -4 e 3:
![-3k - 3 + 4 -3k - 3 + 4](https://tex.z-dn.net/?f=-3k+-+3+%2B+4)
![(4 - 3) - 3k (4 - 3) - 3k](https://tex.z-dn.net/?f=%284+-+3%29+-+3k)
Fazendo:
![4 - 3 = 1 4 - 3 = 1](https://tex.z-dn.net/?f=4+-+3+%3D+1)
![1 - 3k 1 - 3k](https://tex.z-dn.net/?f=1+-+3k)
Então:
Primeiro substituimos
Agora, é só fazer:
Então:
Para
Substituindo
Fazendo:
Então:
Para
Substituindo
Fazendo:
Então:
Para
Substituindo
Distribuíremos
Agruparemos -4 e 3:
Fazendo:
Então:
Respondido por
25
Resposta:
f ( k+1) = 1- 3k
Explicação passo-a-passo:
Perguntas interessantes